Quantifying Molecular Dynamics within Complex Cellular Morphologies using LLSM‐FRAP (Small Methods 6/2022). Issue 6 (15th June 2022) - Colin‐York, Huw; Heddleston, John; Wait, Eric; Karedla, Narain; deSantis, Michael; Khuon, Satya; Chew, Teng‐Leong; Sbalzarini, Ivo F.; Fritzsche, Marco
Abstract : Front Cover In article number 2200149, Colin‐York, Fritzsche, and co‐workers found that by combining lattice light sheet microscopy (LLSM), fluorescence recovery after photo‐bleaching (FRAP), and numerical simulations, LLSM‐FRAP provides a means of quantifying molecular dynamics within complex 3D cell morphologies.